A Deep Insight Into Regulatory T Cell Metabolism in Renal Disease: Facts and Perspectives - Han, Zhongyu; Ma, Kuai; Tao, Hongxia; Liu, Hongli; Zhang, Jiong; Sai, Xiyalatu; Li, Yunlong; Chi, Mingxuan; Nian, Qing; Song, Linjiang; Liu, Chi (Frontiers in Immunology, 2022)
Kidney disease encompasses a complex set of diseases that can aggravate or start systemic pathophysiological processes through their complex metabolic mechanisms and effects on body homoeostasis. The prevalence of kidney disease has increased dramatically over the last two decades. CD4+CD25+ regulatory T (Treg) cells that express the transcription factor Foxp3 are critical for maintaining immune homeostasis and preventing autoimmune disease and tissue damage caused by excessive or unnecessary immune activation, including autoimmune kidney diseases. Recent studies have highlighted the critical role of metabolic reprogramming in controlling the plasticity, stability, and function of Treg cells. It is also likely that they play a vital role in limiting kidney transplant rejection and potentially promoting transplant tolerance. Metabolic pathways, such as mitochondrial function, glycolysis, lipid synthesis, glutaminolysis, and mammalian target of rapamycin (mTOR) activation, are involved in the development of renal diseases by modulating the function and proliferation of Treg cells. Targeting metabolic pathways to alter Treg cells can offer a promising method for renal disease therapy. In conclusion, renal disease is accompanied by significant changes in metabolic patterns, such as changes in glucose, amino acid, and lipid metabolism. This review concludes the relationship between Treg cells and metabolic pathways and explores the role of metabolism in modulating Treg cells in the pathogenesis of some renal diseases.